(untitled) (Journal of Chemical Engineering, 2014)
Chopped jute fiber-epoxy composites with varying fiber length (2-12 mm) and mass fraction (0.05-0.35) had been prepared by a heat press unit. The cross-linked product was characterized in terms of specific gravity, thermal conductivity, tensile strength, Young modulus and elongation at break. The transverse thermal conductivities for randomly oriented fibers in the composite were investigated by Lees and Charltons method. The tensile strength, Young modulus and elongation at break were investigated by a Universal Tensile Tester. With an increase in the fiber content (irrespective of the fiber length), the thermal conductivity of the composite decreases; the decreasing rate being highest for the fiber length of 2 mm followed by that for the fiber length of 6 and 12 mm. The decreasing rate of the thermal conductivity of the jute-epoxy composite is comparatively higher to that reported in literature for acrylic polymer hemp fiber composite. The tensile strength also decreases with the increase of the fiber content in the composite. The fiber length does not show to have significant effect on the tensile strength of the composite; the variation in strength being masked within experimental error. The Young modulus increases with the increase of fiber content within elastic limit; showing the highest values for the fiber length of 6 mm followed by those for the fiber length of 2 mm and 12 mm. The elongation at break shows slightly increasing trend up to 15% fiber content, but beyond that it decreases drastically. The specific gravity decreases with the increase in the fiber content and thus the recalculated specific tensile strength is found to keep at a stable level of 36MPa up to the fiber content of 20%, and beyond that the specific tensile strength decreases with the increase in the fiber content. It is concluded that jute fiber-epoxy composite could be used as a good heat-insulating material. Further investigation is recommended on the improvement of the thermal insulation keeping the mechanical properties unchanged or even improved. The TGA study is also required to ascertain the field of application of the material. DOI: http://dx.doi.org/10.3329/jce.v27i2.17807 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 77-82